Land tenure and land administration in Nigeria and the Cameroons - Meek, Charles Kingsley (London : H. M. Stationery Off., 1957)
The book examines the administration of land tenure system and its impact in both the Northern and Southern Nigeria by the British during the colonial era.
Includes bibliographical references and index.
usc 31/01/2019
Loans
Keywords: Land tenure; Agriculture; Nigeria; Cameroon